2002
DOI: 10.1007/s00261-001-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemosuccus pancreaticus: diagnosis with CT and MRI and treatment with transcatheter embolization

Abstract: We report the case of a 56-year-old woman with a presyncopal episode followed by melena. A sentinel clot sign in the pancreatic duct on precontrast computed tomography and the presence of a splenic artery aneurysm on postcontrast computed tomography strongly suggested a fistula between the aneurysm and the duct, as visualized by magnetic resonance imaging. The patient was treated successfully by complete embolization of the splenic artery aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 11 publications
0
38
1
2
Order By: Relevance
“…Therefore, if patients present with obscure source of repeated upper gastrointestinal bleeding, especially underlying chronic pancreatitis, repeated examinations and careful observations should be performed for the diagnosis of these conditions and HP should be included in differential diagnosis [9] . Koizumi et al [10] reported that MRI successfully identified the fistula and bleeding. However, MRI was not helpful for the diagnosis of HP in our cases, and reasons remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if patients present with obscure source of repeated upper gastrointestinal bleeding, especially underlying chronic pancreatitis, repeated examinations and careful observations should be performed for the diagnosis of these conditions and HP should be included in differential diagnosis [9] . Koizumi et al [10] reported that MRI successfully identified the fistula and bleeding. However, MRI was not helpful for the diagnosis of HP in our cases, and reasons remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…При остром панкреатите про-теолитические энзимы поджелудочной железы при-водят к локальному воспалению, вследствие которого может происходить окклюзия соседних вен, а также способствуют появлению эрозий стенки артерий и образованию псевдоаневризм селезеночной, пече-ночной, верхней брыжеечной, гастродуоденальной и других артерий [12]. Для диагностики псевдоанев-ризм используют ультразвуковой метод исследова-ния с допплерографией, компьютерную томографию, магнитно-резонансную томографию [13,14]. «Золотым стандартом» диагностики является ангиография, ко-торая позволяет оценить размеры псевдоаневризмы, ее локализацию и осуществить вмешательство [15].…”
Section: Discussionunclassified
“…69,73 Contrast-enhanced computed tomography (CT) scans with angiography and MRI can be helpful in further characterization of the local anatomy and can help lead to the diagnosis in more than 90% of cases. 69,74 Both of these imaging modalities can help distinguish pancreatic masses, aneurysms, or pseudoaneurysms of the local vasculature, or anatomic variants, including pancreatic divisum. Occasionally, CT angiography can identify active bleeding if the rate of bleeding is at least 0.4 mL/ min.…”
Section: Hemosuccus Pancreaticusmentioning
confidence: 99%